Keefektifan Biblioedukasi Berbasis Psikoedukasi Ajaran KH Ahmad Dahlan Untuk Meningkatkan Kedamaian Siswa - Kurniawan, Setyo Adi; Saputra, Wahyu Nanda Eka (Universitas Muria Kudus, 2025)
This study aimed to examine the effectiveness of biblioeducation based on KH Ahmad Dahlan’s teachings in promoting student peace. The research involved grade XII students of SMK Muhammadiyah 1 Muntilan using a quasi-experimental design, specifically the Pretest-Posttest Control Group Design. Sixteen students participated, divided into an experimental group (8 students) receiving biblioeducation treatment and a control group (8 students) without treatment. A peace scale was utilized as the research instrument to measure student peace levels before and after the intervention. Hypothesis testing was conducted using a T-test to assess the significance of differences between the two groups. The T-test results revealed a significant improvement in the experimental group compared to the control group. The findings demonstrated that biblioeducation based on KH Ahmad Dahlan’s teachings effectively enhanced student peace, with the experimental group showing a higher increase in peace scores than the control group.